The ecology of the Barí : rainforest horticulturalists of South America - Beckerman, Stephen (University of Texas Press, 2013)
This book is a study of the human ecology of the Barí, drawing on more than forty years of field research to examine relations with natural and social environments, reactions to depredations and warfare, and belief in the possibility that a child can have dual paternity.